A Study on the Application of Signaling Effects in Strategic Human Resource Information Disclosure - Fengzhen Xu (MultiTech Publisher, 2026)
Strategic human resource information disclosure has emerged as an important mechanism through which firms communicate their human capital quality and management capabilities to external stakeholders. Drawing upon signaling theory, this study develops a theoretical framework to examine how signaling effects operate in the context of strategic human resource disclosure. The analysis identifies three distinct signaling mechanisms: signaling to capital markets regarding firm value, signaling to labor markets regarding employment conditions, and signaling to internal stakeholders regarding organizational commitment. The study further explores the conditions under which HR disclosure signals are credible, including signal costliness, observability, and imitation difficulty. Boundary conditions that moderate signaling effectiveness are examined, including firm characteristics, disclosure attributes, and stakeholder characteristics. The theoretical framework reveals that HR disclosure signals may have differential effects on multiple receiver groups, creating potential trade-offs for firms. The study contributes to the literature by providing a comprehensive theoretical account of signaling mechanisms in HR disclosure and offers implications for both research and practice.